Peran World Trade Organization WTO Dalam Penyelesaian Sengketa Perdagangan Internasional - Sapanah, Mawar (Media Hukum Indonesia (MHI), 2026)
The World Trade Organization (WTO) is an international trade organization that plays an important role in regulating, facilitating, and resolving trade disputes between countries. This study aims to understand the role of the WTO in resolving international trade disputes and to examine the dispute settlement mechanisms that apply within the WTO framework. The research uses a normative juridical method by examining secondary data in the form of literature, journals, scientific articles, and relevant international legal provisions. The results of the study show that the WTO has two main roles in dispute settlement, namely a legislative role through the regulation of various international trade agreements and an adjudicative role through consultation forums, panels, appellate bodies, and the implementation of decisions. The WTO dispute settlement mechanism is implemented through consultation, panel formation, panel report ratification, appeal process, and implementation of decisions by member countries. With this mechanism, the WTO is able to provide legal certainty and encourage the creation of an orderly, transparent, and fair global trading climate.